Molecular Dynamics Simulation of Bioactive Compounds Against Six Protein Target of Sars-Cov-2 As Covid-19 Antivirus Candidates - Fikry Awaluddin; Irmanida Batubara; Setyanto Tri Wahyudi (Jurnal Kimia Valensi, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the virus that causes Coronavirus 2019 (COVID-19). To date, there has been no proven effective drug for the treatment or prevention of COVID-19. A study on developing inhibitors for this virus was performed using molecular dynamics simulation. 3CL-Pro, PL-Pro, Helicase, N, E, and M protein were used as protein targets. This study aimed to determine the stability of the selected protein-ligand complex through molecular dynamics simulation by Amber20 to propose bioactive compounds from natural products that have potential as a drug for COVID-19. Based on our previous study, the best value of free binding energy and protein-ligand interactions of the candidate compounds are obtained for each target protein through molecular docking. Corilagin (-14.42 kcal/mol), Scutellarein 7-rutinoside (-13.2 kcal/mol), Genistein 7-O-glucuronide (-10.52 kcal/mol), Biflavonoid-flavone base + 3O (-11.88 and -9.61 kcal/mol), and Enoxolone (-6.96 kcal/mol) has the best free energy value at each protein target. In molecular dynamics simulation, the 3CL-Pro-Corilagin complex was the most stable compared to other complexes, so that it was the most recommended compound. Further research is needed to test the selected ligand activity, which has the lowest free energy value of the six target proteins.